2021
DOI: 10.1002/ppul.25545
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of surfactant administration via thin catheter in preterm infants with neonatal respiratory distress syndrome: A systematic review and meta‐analysis

Abstract: Objective: The efficacy and safety of surfactant administration via thin catheter in preterm infants with neonatal respiratory distress syndrome (NRDS) was investigated.Methods: PubMed, Embase, Cochrane Library, and Web of Science databases were searched to identify randomized controlled trials (RCTs) that comparing thin catheter technique with intubation for surfactant delivery in preterm infants with NRDS.Results: Thirteen RCTs (1931 infants) were included in the meta-analysis. The use of thin catheter techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
1
8
0
1
Order By: Relevance
“…When selecting documents, the titles and abstracts would be first read to exclude irrelevant documents, and then the full text would be read to determine whether they could be included. The main content of data extraction was: (1) We also used the Newcastle-Ottawa Scale (NOS) to evaluate the methodological quality and risk of bias of included literature. The scale includes three columns including the selection of study subjects, comparability between groups, exposure or outcome evaluation, with a maximum score of nine points.…”
Section: Data Extraction and Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…When selecting documents, the titles and abstracts would be first read to exclude irrelevant documents, and then the full text would be read to determine whether they could be included. The main content of data extraction was: (1) We also used the Newcastle-Ottawa Scale (NOS) to evaluate the methodological quality and risk of bias of included literature. The scale includes three columns including the selection of study subjects, comparability between groups, exposure or outcome evaluation, with a maximum score of nine points.…”
Section: Data Extraction and Outcomesmentioning
confidence: 99%
“…Neonatal respiratory distress syndrome (NRDS), formerly known as hyaline membrane disease (HMD), is a clinical syndrome characterized by respiratory distress and progressive aggravation soon after birth (1), mostly due to insufficient pulmonary surfactant secreted by alveolar type II epithelial cells, which is more common in premature infants in clinical practice (2). Neonates with younger gestational age tend to suffer from a higher incidence rate, lighter weight, and a higher fatality rate (3).…”
Section: Introductionmentioning
confidence: 99%
“…Systematic literature reviews and meta-analyses comparing the LISA technique with mechanical ventilation, INSURE, or nasal CPAP alone have shown that LISA is associated with significantly improved outcomes for BPD or death and a reduced need for mechanical ventilation within 72 hours of birth [15,[18][19][20]36,37]. Failure of LISA was associated with younger gestational age (<28 weeks) and/or lack of prenatal steroids rather than the procedure itself or the surfactant used [29].…”
Section: Lisa: Past Clinical Evidence and Current Research Gapmentioning
confidence: 99%
“…Surfactant reflux is another outcome warranting more robust research since some groups have observed increased instances of reflux or bradycardia with LISA compared to INSURE when examining various types of surfactants [18,19,36]. Others have noted their expectation to observe higher rates of reflux with largervolume surfactants when utilizing LISA [24]; however, studies of the larger-volume surfactants such as bovine lipid extract surfactant (BLES) and Neosurf (5 mL/kg, 135 mg phospholipids per kg) administered with LISA have generated inconsistent data regarding reflux and reflux-related outcomes [45,56].…”
Section: Evidence Gaps and Future Directionsmentioning
confidence: 99%
“…Respiratory distress syndrome (RDS) is a clinical syndrome characterized by respiratory distress and progressive aggravation in affected neonates soon after birth and is one of the most common clinical conditions dealt with in the neonatal intensive care unit (NICU) (1). It is estimated to affect up to 7% of neonates and is among the major causes of neonatal mortality (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%